Marine Polysaccharide-Collagen Coatings on Ti6Al4V Alloy Formed by Self-Assembly; Micromachines; Vol. 10, iss. 1 - Norris K. Karl; Mishukova O. I. Oksana Igorevna; Zykwinska A. Agata; Colliec-Jouault S. Sylvia; Sinquin C. Corinne; Koptioug A. V. Andrei; Cuenot S. Stephane; Kerns J. D. Jemma; Surmeneva M. A. Maria Alexandrovna; Surmenev R. A. Roman Anatolievich; Douglas T. E. L. Timothy (2019, 2019)
Title screen